Percutaneous Endoscopic Decompression in Lumbar Canal and Lateral Recess Stenosis – The Surgical Learning Curve - Chul-Woo Lee; Kang-Jun Yoon; Sung-Won Kim (Neurospine, 2019)
Objective The purpose of this study is to characterize the learning curve of endoscopic lumbar decompression based on peri- and postoperative parameters and to suggest the potential of full endoscopic decompression as a primary treatment option for lumbar canal and lateral recess stenosis. Methods The records of 223 consecutive patients who underwent percutaneous endoscopic decompression by a single surgeon for their lumbar canal and lateral recess stenosis were reviewed. Patients were stratified into group 1 (n=100) and group 2 (n=123), depending on their case number. After the 100th case, the procedural time reached a plateau and subsequent patients were assigned to the second group. Demographics and surgical outcomes, including operative times, change in dural sac dimensions, length of hospital stay, and intraoperative complication rates were compared between the 2 groups. Postoperative clinical outcomes, including the visual analogue scale (VAS), the Oswestry Disability Index (ODI) and reoperation rates were compared between the 2 groups (group 1, n=90; group 2, n=110) by follow-up evaluation. Results Procedural times were greater in group 1 than group 2 (group 1, 105.26 minutes; group 2, 67.65 minutes; p<0.05) and they had higher complication rates (group 1, 16% [16 of 100]; group 2, 8.3% [8 of 123]; p<0.05). The length of hospitalization, postoperative improvement in VAS and ODI, and reoperation rates were not different between the groups. In both groups, stenotic spinal canals were effectively decompressed. Conclusion Continued surgical experience was associated with a reduction in operative times and less intraoperative complications. Although the learning curve was steep and additional surgical experience may be needed to overcome the learning curve, percutaneous full endoscopic lumbar decompression is a safe, clinically-feasible, and effective surgical technique and can be adopted as the primary treatment for lumbar canal and lateral recess stenosis.